Magelonidae (Polychaeta) from Hong Kong, China, with discussions on related species and redescriptions of three species - Mortimer, Kate; Mackie, Andrew S.Y. (Zoosymposia, 2007)
A review of the Magelonidae from three surveys carried out in Hong Kong waters revealed the presence of three species: Magelona crenulifrons Gallardo, 1968, Magelona cornuta Wesenberg-Lund, 1949, and Magelona cf. cincta. Type materials of M. crenulifrons and M. cornuta were examined and redescriptions undertaken. Magelona cornuta was shown to possess a crenulate anterior margin, and the nature of the thoracic neuropodial lamellae was found to differ from the original description. Comparison with M. crenulifrons revealed these two species to be very morphologically similar, differing however, in several features that require close examination, including the dentition of the abdominal hooks. The presence of a species matching the description of Magelona cincta led to a redescription of the type specimen. Whilst the Hong Kong material shared many similarities with the holotype, several differences were noted. However, due to size variation between the material, the species cannot be currently described as new and is treated separately herein. Material collected from the Gulf of Oman was subsequently studied and revealed the presence of M. crenulifrons off Iran and Qatar, however, M. cornuta which was originally described from Iranian waters, was not present. Additional information has been added to species descriptions and the relationship between Indo-West Pacific species discussed.
World Polychaeta Database (WPolyDb). Open access.